The effect of chronic obstructive pulmonary disease on the level of homocysteinemia and the condition of coronary vessels in patients with myocardial infarction - T. V. Prokofieva; E. A. Lipnitskaya; B. Yu. Kuzmichev; O. S. Polunina; L. P. Voronina; E. A. Polunina (Туберкулез и болезни лёгких)
Objective: to study and compare the level of homocysteine with the results of coronary angiography in patients with myocardial infarction (MI) and concurrent chronic obstructive pulmonary disease (COPD).Subjects and methods. 246 patients with MI were examined. In 137 (55.7%) people, MI developed on the background of COPD, while in 109 (44.3%) patients MI was a single condition. Comparison groups consisted of 55 somatically healthy individuals and 50 patients with COPD. Enzyme immunoassay was used for testing homocysteine levels in plasma samples.Results. Stenoses of only one coronary artery (CA) with hyperhomocysteinemia were rare in patients in both groups (3.5% in patients with myocardial infarction and 3% in patients with myocardial infarction and concurrent COPD), multivessel diseases of CA statistically significantly prevailed. Lesions of 3 vessels or more were detected statistically significantly more often in patients with hyperhomocysteinemia with myocardial infarction and concurrent COPD. Among patients with myocardial infarction with hyperhomocysteinemia, patients with CA narrowing by 50-75% prevailed, and among patients with myocardial infarction with COPD and hyperhomocysteinemia, patients with CA narrowing by 75-99% and complete occlusion were statistically significantly more frequent. That is, in patients with myocardial infarction, concurrent COPD and hyperhomocysteinemia, more pronounced lesion of CA was observed, which was manifested by multivascular lesions, greater severity of occlusion and higher frequency of complete stenosis of CA.